The Incipits of Semi-Popular Articles about Language Learning - Yolanda Puteri Madani; I Wayan Darya (Stairs, 2021)
This study aims to identify the type of organization incipit used and analyze the language features of organization incipit in semi-popular science article. This research was conducted by using qualitative methods and employs a corpus-driven analysis approach. The approaches are conducted by adopting Hyland’s framework of proximity, specifically the organization facet of incipits position. After analyzing the data, the study found incipits in the semi-popular article can be broadly categorized into 5 categories and the most used category is ‘research finding’, followed by ‘establishment of a common ground’, then ‘contextualization of the article’, after that is ‘research problem’ category, and the least identified category is ‘benefit of the finding’. This study also found language feature of each category, like word frequency, concordance, and content organization is the one that identifies each category from the other.